LARVICIDAL EFFICACY OF MATURE LEAF EXTRACT OF NICOTIANA PLUMBAGINIFOLIA VIV. (SOLANACEAE) AGAINST SOUTHERN HOUSE MOSQUITO - ANIKET SINGH,; KUNTAL BHATTACHARYA,; ANUSHREE SINGH RAY,; GOUTAM CHANDRA, (International Journal of Pharma and Bio Sciences, 2016)
The small iniquitous fly mosquito is responsible for transmitting various deadly diseases, so it is inevitable to control mosquito vector population. Due to resistance of the synthetic insecticides, use of botanicals is a new trend to control the mosquito species. Present study was carried out to examine the efficacy of mature leaf extract of Nicotiana plumbaginifolia on larval forms of filarial vector Culex quinquefasciatus. All larval instars treated with crude and three different solvent extracts of N. plumbaginifolia leaves. LC50 and LC90 values were determined by log-probit analyses. Statistical justifications were carried out through regression and ANOVA analyses. Cent percent larval mortality was found against 1st instar larvae at 0.20% concentration of crude extract and 60 ppm concentration of acetone solvent extract at 72h of post exposure. Non-target organisms were non-responsive to both crude and acetone solvent extracts. Thus, N. plumbaginifolia may act as potential larvicidal agent against Cx. quinquefasciatus.